The Linguistic Characteristics of the Form –Ayotgan Bo‘Lsa and its Changes (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
In the article, the linguistic features of the form of -ayotgan bo‘lsa and its change are analyzed. Linguistic (paradigmatic) feature of the form -yyung bolsa consists of conditional, present tense, continuation patterns and relationship (syntactic feature). If necessary, one or the other meaning of the form of "-ayotgan bo‘lsa" is strengthened and concretized with the help of a dictionary tool. This is done in a clarifying context. In the clarifying context for the conditional term, this term is emphasized and strengthened by means of the auxiliary words agar, bordi-yu, basharti, mabodo, magar. These words are synonymous with the form -yungola, or more precisely, the -sa part of this form, and serve to express connotation: Relevant symbols and syntactic features are defined in the form itself, and the context for their expression is neutral enough - ayotgan bo‘lsa the form is imperative, it is also used in contexts that are inconvenient due to the present tense and syntactic features.